Gender Differences in Patient‐Reported Outcomes Among Adults With Atherosclerotic Cardiovascular Disease. Issue 24 (18th December 2018) - Okunrintemi, Victor; Valero‐Elizondo, Javier; Patrick, Benjamin; Salami, Joseph; Tibuakuu, Martin; Ahmad, Saba; Ogunmoroti, Oluseye; Mahajan, Shiwani; Khan, Safi U.; Gulati, Martha; Nasir, Khurram; Michos, Erin D.
Abstract : Background: Atherosclerotic cardiovascular disease (ASCVD) accounts for approximately one third of deaths in women. Although there is an established relationship between positive patient experiences, health‐related quality of life, and improved health outcomes, little is known about gender differences in patient‐reported outcomes among ASCVD patients. We therefore compared gender differences in patient‐centered outcomes among individuals with ASCVD. Methods and Results: Data from the 2006 to 2015 Medical Expenditure Panel Survey, a nationally representative US sample, were used for this study. Adults ≥18 years with a diagnosis of ASCVD, ascertained by International Classification of Diseases, Ninth Revision ( ICD‐9) codes and/or self‐reported data, were included. Linear and logistic regression were used to compare self‐reported patient experience, perception of health, and health‐related quality of life by gender. Models adjusted for demographics, socioeconomic status, and comorbidities. There were 21 353 participants included, with >10 000 (47%‐weighted) of the participants being women, representing ≈11 million female adults with ASCVD nationwide. Compared with men, women with ASCVD were more likely to experience poor patient–provider communication (odds ratio 1.25 [95% confidence interval 1.11–1.41]), lower healthcare satisfaction (1.12 [1.02–1.24]), poor perception of health status (1.15 [1.04–1.28]), and lower health‐related quality of life scores. Women with ASCVD also had lower use of aspirin and statins, and greater odds of ≥2 Emergency Department visits/y. Conclusions: Women with ASCVD were more likely to report poorer patient experience, lower health‐related quality of life, and poorer perception of their health when compared with men. These findings have important public health implications and require more research towards understanding the gender‐specific differences in healthcare quality, delivery, and ultimately health outcomes among individuals with ASCVD.